Effect of Different Fertilizer Packages on the Performance of Jhum Crops - Bala, T. K.; Paul, A. K.; Karim, A. J. M. S. (International Journal of Bio-resource and Stress Management, 2016)
An experiment was conducted at Hill Agricultural Research Station, Khagrachari, Bangladesh during May, 2014 to January, 2015 to study the effects of different fertilizer on the performance of jhum crops. Rice, marpha, maize, sweet gourd, sesame and arhar were used as the jhum test crops. The experiment was laid out in Latin Square Design (LSD). The treatments consisted of four levels of NPK fertilizers i.e. no fertilizer (Control), 40 kg N+25 kg P2O5+30 kg K2O ha-1, 80 kg N+50 kg P2O5+60 kg K2O ha-1 and 120 kg N+75 kg P2O5+90 kg K2O ha-1. The yield parameters and yields of jhum crops were significantly affected by fertilizer. NPK fertilizer plays a significant role on the yield of rice, marpha, maize, sesame, sweet gourd and arhar. The highest yield of rice (3.34 t ha-1), marpha (984.8 kg ha-1), maize (951.3 kg ha-1), sweet gourd (1418.0 kg ha-1), sesame (331.3 kg ha-1) and arhar (349.9 kg ha-1) were found in T4 treatment that received 120 kg N+75 kg P2O5+90 kg K2O ha-1. On the other hand, lowest yield of rice (1.67 t ha-1), marpha (453.8 t ha-1), maize (517.5 t ha-1), sweet gourd (781.3 t ha-1), sesame (107.1 t ha-1) and arhar (103.6 t ha-1) were found in the treatment with no fertilizer.